Supervised news topic detection - Gaur, Mokshika (2016)
With the advancement of technology, there has been much improvement in the automatic recording of broadcast news by utilizing speech recognition. However the continually increasing dynamic information pool is posing challenges for efficient information retrieval techniques. This pain-point creates the need to develop systems that can automatically categorize this information under relevant topics for the purpose of easy information retrieval.